Let's get lost - Alsaid, Adi (Harlequin Teen, 2014)
During her cross-country adventures following the tragic death of her family, Leila touches the lives of four strangers -- Hudson, Bree, Elliot, and Sonia. While forever changing the lives of these four, Leila also discovers an important truth about herself.